Fomentando el desarrollo local con estrategias innovadoras de negocios inclusivos y sostenibles. - Jael Janine Sarmiento Torres; Angélica María Carvajal Guerrero; Balmes Leandro López (Mundo Fesc)
The socioeconomic inclusion of BOP businesses is a fundamental factor in promoting equity and sustainable development. Given the limited availability of finance and resources, these businesses, which are part of the low-income population, face challenges in accessing economic and social opportunities. To address this challenge, governments and non-governmental organizations need to adopt more comprehensive, equitable, and inclusive strategies in the region. The objective of this research is to analyze the barriers and opportunities faced by this segment of the population, proposing effective strategies to address resource scarcity and promote their inclusion in the business world. A methodology with a critical social approach and a descriptive scope is chosen, considering the contextual and environmental conditions of local cooperatives within the framework of inclusion for BOP businesses. It is essential to understand the city's social, economic, and commercial environment, employing descriptive research to identify specific community characteristics . This approach will provide a comprehensive view of the city's economic health and facilitate the creation of a comprehensive plan to promote inclusion and sustainable development. The analysis will focus on the industry, size, structure , and inclusive business models of local cooperatives, where the entrepreneurial component of the base-of-the-pyramid enterprises must be strengthened to achieve the objectives set. The results obtained are anticipated to significantly contribute to socioeconomic inclusion, sustainable progress , and equity in Cúcuta by effectively addressing the barriers and opportunities facing low- income enterprises. This research seeks to generate valuable information for the formulation of policies and business practices that promote inclusion and sustainable development in similar settings.